1998
DOI: 10.1093/humupd/4.5.710
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of integrin adhesion molecules in endometriosis and human endometrium

Abstract: Integrins are cell adhesion molecules that undergo cell-specific dynamic changes during the normal menstrual cycle in the human endometrium. Here, using immunohistochemistry, we have investigated the expression pattern of the integrins alphav, alpha2beta1, alpha3beta1, alpha3, alpha6, beta1, beta2 and beta3 in the human ectopic endometrium of 30 patients and in nine cases in the corresponding eutopic endometrium. The biopsies were obtained during the early or late follicular phase (25 cases), during the corpus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 26 publications
1
20
0
2
Order By: Relevance
“…In the present study we found that expression of claudin-3 and claudin-4 in eutopic endometrium from women with endometriosis was lower compared with normal endometrium from women without endometriosis, but the difference was not statistically significant. This result agrees with that from a previous study, in which no difference was found in integrin expression between endometrium from women with and without endometriosis (21). In contrast, some evidence has suggested that the eutopic endometrium from women with endometriosis has altered expression of several components of the junctional complexes, such as connexin, cadherin, and catenin (22,23).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study we found that expression of claudin-3 and claudin-4 in eutopic endometrium from women with endometriosis was lower compared with normal endometrium from women without endometriosis, but the difference was not statistically significant. This result agrees with that from a previous study, in which no difference was found in integrin expression between endometrium from women with and without endometriosis (21). In contrast, some evidence has suggested that the eutopic endometrium from women with endometriosis has altered expression of several components of the junctional complexes, such as connexin, cadherin, and catenin (22,23).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, cancercell migration promoting collagen triple helix repeat containing 1 (CTHRC1) [37] and Rho GTPase activating protein (ARHGAP) family genes, which are implicated in actin remodeling, cell polarity and migration [38], were up-regulated in the endometriosis group. We also observed a 3-fold down-regulation of integrin alpha 1 subunit (ITGA2), which changes cell-cell and cell-matrix interactions that are important for the development of endometriosis [39]. We thus found aberrant mRNA levels of several novel genes associated with cell migration and cell adhesion: ADAM23, ITGB5, FNDC1, CTHRC1 and ARHGAP25.…”
Section: Cell-to-cell Signaling Interaction and Cellular Movementmentioning
confidence: 79%
“…The a V b 3 integrins transmit signals to the cytoskeletal structures of cells and usually mediate expression of fibronectin and vibronectin (31) and have been localized in endometriotic lesions and endometrium in women with and without endometriosis during both follicular or secretory phases (32). Therefore, we hypothesise that a V b 3 integrin may facilitate the adhesion of endometrial cells, especially during menstruation to the pelvic peritoneum, and lead to the development of endometriosis.…”
Section: Figurementioning
confidence: 97%